1997
DOI: 10.1002/(sici)1097-0274(199703)31:3<353::aid-ajim12>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome aberrations in hospital workers: Evidence from surveillance studies in Italy (1963–1993)

Abstract: Hospital workers are occupationally exposed to various agents known or suspected to induce chromosome damage, the most studied being ionizing radiation. To determine the extent of chromosome damage in peripheral blood lymphocytes in this population, taking into account temporal changes and job titles, a re‐analysis of cytogenetic studies performed in four Italian laboratories in the period 1965–1993 was carried out. A total of 871 hospital workers and 617 controls, mainly coming from ad hoc studies or surveill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…CBMN assay endpoints are not specific to the biological effects of radiation. Bonassi et al [7] suggested that other chromosome-damaging agents might be involved in the increase in chromosome aberrations observed in the workers with uncertain exposure to IR. The working environment in hospitals is complex and includes, besides ionizing radiation, several chemical pollutants that may have genotoxic effects; thus, the possibility that the observed MNs may be partly due to chemical pollutants present in the hospital environment cannot be excluded, even if the difference between those radiation-exposed workers who reported such co-exposure and those who did not was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CBMN assay endpoints are not specific to the biological effects of radiation. Bonassi et al [7] suggested that other chromosome-damaging agents might be involved in the increase in chromosome aberrations observed in the workers with uncertain exposure to IR. The working environment in hospitals is complex and includes, besides ionizing radiation, several chemical pollutants that may have genotoxic effects; thus, the possibility that the observed MNs may be partly due to chemical pollutants present in the hospital environment cannot be excluded, even if the difference between those radiation-exposed workers who reported such co-exposure and those who did not was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Many cytogenetic studies have been conducted among hospital workers exposed to IR. Bonassi et al [7] observed increased rates of chromosomal aberrations in hospital workers exposed to IR. A low, but statistically significant, increase in the rate of chromosomal aberrations in circulating lymphocytes among hospital workers with thyroid nodules was also observed in workers occupationally exposed to radiation [8].…”
Section: Subjectsmentioning
confidence: 99%
“…In their meta-analysis of cytogenetic studies performed in four Italian laboratories in the period 1965-1993, Bonassi et al (11) reported significantly higher frequencies of chromosome aberrations for various job titles in medical workers exposed to low doses of ionising radiation. Garaj-Vrhovac et al also reported higher rates of chromosome aberrations in workers exposed to ionising radiation but differences between various job titles were not significant (16).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that cancer incidence among healthy individuals of a population increases with increased levels of CAs in their circulating lymphocytes (Bonassi et al, 2000(Bonassi et al, , 2004. Because an increased frequency of CAs was found to be a sensitive indicator of exposure to IR (Carrano and Natarajan, 1988), the CAs assay has been applied to monitor workers professionally exposed to low but cumulative levels of IR (Lazutka et al, 1999;Zakeri and Hirobe, 2010;Bonassi et al, 1997;Maffei et al, 2004;Ballardin et al, 2007). Analogously to CAs assay, the SCEs analysis is widely used to assess the genomic damage, because it represents a sensitive method for identifying physical DNA-damaging agents that directly induce DNA strand breaks (Natarajan and Mullenders, 1987).…”
Section: Introductionmentioning
confidence: 99%